Chapter 11 Supplanting Anthropocentric Legalities Can the Rule of Law Tolerate Intensive Animal Agriculture? - Deckha, Maneesha (Taylor & Francis, 2024)
This chapter explores how the rule of law can support emergent legislative proposals in a handful of jurisdictions around the world to curtail intensive animal farming. Part 1 reviews the global emergence of these legislative proposals to date and identifies their common features or themes, as well as their limited success. Part 2 then discusses the pliability of the rule of law to serve as an agent of social change in general as well as in the realm of intensive farming. It explains how the rule of law can be a persuasive discursive legal tool in generating actual legal regulation to address social problems such as intensive farming and connects the analysis to broader questions regarding norm development in international law. Drawing on posthuman feminist theory, the chapter contributes to the growing field of global animal law that explores animal law issues through international law and transnational law frameworks, by highlighting the potential of the rule of law to challenge the legitimacy of at least some forms or portion of animal-based food systems. The chapter seeks to add to the developing conversation as to how to supplant existing anthropocentric legal norms through innovative deployment of new legal arguments in favor of animals.